Hubungan Ekspresi Emosi Orang Tua dengan Tingkat Depresi pada Remaja: Studi pada Siswa MTs Al-Washliyah Medan Krio - Muhammad Najari; Milfa Yetty; Rahmi Utami (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2024)
Adolescent depression has become an important mental health issue because of its impact on adolescents’ psychological, social, and academic development. Family emotional climate, particularly Parental Expressed Emotion (PEE), has been identified as one of the factors associated with adolescent mental health. This study aimed to examine the relationship between parental expressed emotion and depression levels among students at MTs Al-Washliyah Medan Krio. A quantitative correlational design was employed involving 105 students selected from a population of 155 students. Data were collected using Likert-scale questionnaires measuring parental expressed emotion and adolescent depression. The data were analyzed using descriptive statistics and Pearson Product-Moment correlation after meeting the required statistical assumptions. The findings indicated that parental expressed emotion had a significant relationship with adolescents’ depression levels (r = 0.4619, p < 0.05). These findings suggest that the quality of parents’ emotional expression is associated with adolescents’ psychological well-being. Strengthening positive emotional communication within families may therefore contribute to efforts aimed at preventing depression among adolescents.